(untitled) (Current Horticulture, 2024)
A study was undertaken to determine physio-chemical properties of fruits and to evaluate the best accession of jalpai (Elaeocarpus floribundus Blume.) during fruiting season of 2016 at Department of Post-harvest Technology, UBKV, Pundibari, West Bangal. The fruits were harvested from distinct locations of North Bengal and were brought to the lab for their biochemical analysis. ACC-11 had a very highest value of TSS (7.07° Brix), along with ACC-25 (6.9°Brix). The ACC-24 had high fruit weight (20.83 g) compared to other accessions. ACC-30 also showed a highest value of total sugar (7.50) and high reducing sugar content (2.35). ACC-20 not only had a high TSS value but also had higher amount of total sugar content (6.85). Similar trend was observed in ACC-29 where high TSS (18.7), high reducing sugar (2.17) and total sugar content (5.77) were recorded. Thus, ACC-11, ACC-20 and ACC 29, yield superior quality of jalpai, whereas ACC-30 produces fruits with high sugar and acid content.